Computational approach to determine the combination of polyherbs based on the interaction of their metal complexes on the mucoadhesive properties of type II mucin - Eka Diyah Putri Lestari, Sri Widyarti, Djoko Herry Santjojo, Nashi Widodo, Sutiman Bambang Sumitro (Journal of Applied Pharmaceutical Science, 2023)
Mucin is the main mucus component besides water, which comes from the glycoprotein group. Mucoadhesive properties can be analyzed based on the binding interactions between compounds and mucin in mucus. This research is an in-silico approach aiming to obtain bioactive compounds that have a stable interaction with mucin-type II (MUC2) by screening ten compounds used in Indonesian herbal medicines. Molecular docking was used as a procedure for forming the compound-mucin complexes. Furthermore, molecular dynamic simulation with YASARA Dynamics software was used to obtain the stability of compound-mucin complexes. The curcumin-metal ions and kaempferol-metal ions complexes showed the most stable binding affinity and interaction with MUC2 compared to eight other ligands. Based on the molecular dynamic simulation, kaempferol-metal ions complexes are predicted to interact in the D3 chain, while curcumin-metal ions complexes more stably interact with the CysD1 chain. Both complex interactions simultaneously strengthen and synergize interactions with MUC2. Herbs containing one or both bioactive compounds, curcumin, and kaempferol are supposed to be composed into a polyherbal composition to obtain optimal mucoadhesive properties for MUC2.